Characterization of urinary protein profile in regular kratom (Mitragyna speciosa korth.) users in Malaysia. Issue 2 (3rd April 2022) - Jasim, Rana Khudhair; Hassan, Zurina; Singh, Darshan; Boyer, Edward; Gam, Lay-Harn
Abstract: Mitragyna speciosa (Korth.) also known as kratom or ketum has been traditionally used for its diverse medicinal value in Southeast Asia. Despite of its therapeutic value, kratom's safety profile remains deficiently elucidated. Our study aims to characterize the urinary protein profile of regular kratom users to determine its toxic effects on renal functioning. A total of 171 respondents (comprising of n = 88 regular kratom users, and n = 83 healthy controls) were recruited for this study. Urine specimens were collected and analyzed using SDS-PAGE, followed by LC/MS/MS analysis. Our results show albumin is the primary, and most abundant form of protein excreted in kratom user's urine specimens (n = 60/64), indicating that kratom users are predisposed to proteinuria . Kratom users had an elevated urinary protein (with an intensity of 66.7 kDa band), and protein: creatinine ratio (PCR) concentrations relative to healthy controls. However, kratom user's urinary creatinine concentration was found to be in the normal range as the healthy control group. While, kratom users who tested positive for illicit drug use had an elevated urinary albumin concentration. Our preliminary findings indicate that regular consumption of freshly brewed kratom solution over a protracted period (for an average of eleven years) seems to induce proteinuria, suggestive of an early stage of kidney injury. Hence, further studies are urgently needed to confirm our findings, and establish kratom's renal impairing effects.